Analisis Perencanaan Pajak Penghasilan Pasal 21 Untuk Mengoptimalkan Penghematan Pajak Penghasilan Badan Pada Pt Infra Digital Nusantara Jakarta Tahun 2021 - Fathiyah Choirunnisa; Chairil Anwar Pohan (Institut Ilmu Sosial dan Manajemen STIAMI, 2023)
The phenomenon that occurs at PT Infra Digital Nusantara, is in the calculation of Article 21 income tax, the company takes practical steps using the gross method so that there are no corporate income tax savings. This study has a concern on three issues they are, the application of tax planning as an effort to optimize employee income tax at PT Infra Digital Nusantara in 2021, the tax planning carried out is in accordance with applicable tax regulations, and the corporate tax savings obtained as implications of the gross-up method strategy applied. The research method used is a qualitative descriptive approach using data collection techniques by means of observation, interviews, documentation and triangulation. The results of the study indicate that PT Infra Digital Nusantara has carried out Article 21 income tax planning well. Does not violate tar provisions, in the business is already rational and has been supported by adequate supporting evidence. Tax planning in the calculation of income tax Article 21 carried out by PT Infra Digital Nusantara with the gross method has been in accordance with the provisions of taxation formally and materially. There is no corporate income tax savings on income tax Article 21 planning with the gross up method carried out at PT Infra Digital Nusantara, but tax savings can be obtained for the following tax year. For a loss of Rp11,866,031,959 in 2021, which is greater than 4.02%, it can compensate for the company's profits in the following years, so that the payment of corporate tax can be lower